2015
DOI: 10.3945/ajcn.115.107045
|View full text |Cite
|
Sign up to set email alerts
|

Potential role of milk fat globule membrane in modulating plasma lipoproteins, gene expression, and cholesterol metabolism in humans: a randomized study

Abstract: In contrast to milk fat without MFGM, milk fat enclosed by MFGM does not impair the lipoprotein profile. The mechanism is not clear although suppressed gene expression by MFGM correlated inversely with plasma lipids. The food matrix should be considered when evaluating cardiovascular aspects of different dairy foods. This trial was registered at clinicaltrials.gov as NCT01767077.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
71
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(76 citation statements)
references
References 44 publications
1
71
1
Order By: Relevance
“…Another potential explanation is that this could be partly due to the higher sphingolipid content of cream, 54 since as mentioned above, recent evidence suggests that this may affect the impact of the SFA on the blood lipid profile. 31 Alternatively, the ‘Reduced fat milks and yogurt' consumers may also have been higher consumers of other foods not fully captured by the 11 food groupings used here, and it is possible that some other dietary factor could have resulted in the higher serum triglycerides and total cholesterol observed, such as the percentage energy from carbohydrate. The clusters were based on the patterns of actual intake, which were categorised based on fat content, whereas the tertiles did not distinguish between fat content.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Another potential explanation is that this could be partly due to the higher sphingolipid content of cream, 54 since as mentioned above, recent evidence suggests that this may affect the impact of the SFA on the blood lipid profile. 31 Alternatively, the ‘Reduced fat milks and yogurt' consumers may also have been higher consumers of other foods not fully captured by the 11 food groupings used here, and it is possible that some other dietary factor could have resulted in the higher serum triglycerides and total cholesterol observed, such as the percentage energy from carbohydrate. The clusters were based on the patterns of actual intake, which were categorised based on fat content, whereas the tertiles did not distinguish between fat content.…”
Section: Discussionmentioning
confidence: 94%
“…The absence of association between cheese consumption and blood lipid profiles observed within this analysis is also in agreement with several recent intervention studies, which suggest that the SFA, consumed within the matrix of cheese, may not adversely impact blood lipid profiles. 11, 13, 32, 53 Differences in the calcium contents of different dairy products, 33 and differences in sphingolipid content, 31 are two of the hypotheses that have been put forward to explain these phenomena in previous studies. Further research is required to fully understand the underlying mechanisms of the differences between butter, cream, cheese and milk in their cholesterol-raising abilities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In humans, milk SM also shows potential to improve serum lipids. In a single-blind, randomized, controlled isocaloric parallel study, Rosqvist et al [140] observed that an eight-week consumption of 40 g milk fat/day as whipping cream (rich in MFGM) in overweight adults resulted in lower plasma LDL-C, non-HDL-C, and apoB:apoA-I ratio compared to the same amount of milk fat as butter oil (free of MFGM). Conway et al [141] reported that ingestion of 45 g/day of buttermilk for four weeks resulted in reductions in plasma cholesterol and TG compared to placebo, in a double-blind randomized study of healthy adults.…”
Section: Cardiovascular Diseasementioning
confidence: 99%
“…Lorenzen and Astrup (7) also reported increased fecal excretion of bile acids, possibly due to calcium phosphate binding, thus reducing the enterohepatic recycling of bile acids and resulting in the movement of plasma LDL cholesterol into the liver to support further bile acid synthesis. There is also evidence that dairy products with at least a proportion of the milk fat globule membranes intact will lead to less fat being absorbed (9).…”
mentioning
confidence: 99%